COMPARISON OF DENTAL ANXIETY LEVELS MEASURED USING DENTAL ANXIETY SCALE AND GSR-PSYCHOANALYZER IN PATIENTS AGED 6-8 YEARS OLD - Imamullah, Adil Yuni; Utomo, Rinaldi Budi; Supartinah, Al (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Dental anxiety is a feeling of worrying that something unpleasant or unreasonable will happen during dental and oral care so that the child becomes uncooperative. There are two ways to measure dental anxiety in children subjectively and objectively. Subjectively measured using the Dental Anxiety Scale and objectively using the GSR-Psychoanalyzer. The purpose of this study was to determine the comparison of dental anxiety levels measured using the Dental Anxiety Scale and GSR-Psychoanalyzer in patients aged 6-8 years.Method: Anxiety measurements were carried out in the clinic waiting room before treatment for 32 children aged 6-8 years, consisting of 15 boys and 17 girls. There are 12 children aged 6 years, 9 children aged 7 years, and 11 children aged 8 years. The measurement process was done by the first 16 children using the Dental Anxiety Scale than the GSR-Psychoanalyzer and 16 other children were done the other way around.Result: The Chi-Square test showed that there was no significant difference based on gender with a p-value = 0.233 on the Dental Anxiety Scale and a p-value = 0.760 on the GSR-Psychoanalyzer. Chi-Square test results based on age also showed no significant difference with a p-value = 0.540 on the Dental Anxiety Scale and a p-value = 0.475 on the GSR-Psychoanayzer. The level of dental anxiety as measured using the Dental Anxiety Scale and GSR-Psychoanalyzer in children aged 6-8 years after being analyzed using the Wilcoxon Signed Rank Test, showed no significant difference with p=0.322.Conclusion: There is no difference in the level of dental anxiety based on age and gender as measured using the Dental Anxiety Scale and GSR-Psychoanalyzer